Dinamika Ideologi Pendidikan Indonesia pada Masa Orde Baru hingga Kontemporer: Antara Perubahan dan Keberlanjutan - Mila Trisnawati; Yuliati Yuliati (Jurnal Humanitas: Katalisator Perubahan dan Inovator Pendidikan, 2026)
This article aims to analyze the dynamics of the New Order’s educational ideology in Indonesia and its transformation in the context of contemporary educational liberalization. Using a descriptive qualitative method based on a literature review, this study demonstrates that the New Order regime utilized education as an instrument of political and ideological control through policy centralization, curriculum standardization, and the implementation of militaristic values. Consequently, various forms of resistance emerged from intellectual students, religious institutions, the arts community, and civil society. In the post-New Order era, education underwent a shift toward liberalization marked by privatization, commercialization, and the penetration of neoliberal ideology, which emphasizes efficiency, competition, and market orientation. This study argues that this new ideology subsequently transformed through the emergence of campus managerialism, curriculum marketization, and the reduction of the state’s role, which led to increased inequality and the erosion of humanistic values in education. Nevertheless, resistance from various groups indicates efforts to preserve education as a public right and a democratic space. The findings of this study underscore the need for critical negotiation among the state, the market, and society to realize an inclusive, equitable, and socially just education.